AB0642 Large Vessel Involvement in Limited and Diffuse Systemic Sclerosis: A Pulse Wave Velocity Study. (15th July 2016) - Parisi, S.; Ballini, C.; Priora, M.; Milan, A.; Tosello, F.; Peroni, C.L.; Veglio, F.; Fusaro, E.
Abstract : Background: Systemic Sclerosis (SSc) is a chronic inflammatory autoimmune disease of the connective tissue characterized by vasculopathy and progressive fibrosis thickening of the skin and internal organs. Vascular damage is recognized as a diagnostic landmark in SSc, both in its limited and diffuse form. Micro- and macro-vascular damage have been involved in the pathology; early detection may be helpful in therapeutic planning and management. Subclinical cardiac damage can be detected with transthoracic echocardiography (TTE) while arterial stiffness can be measured by Pulse wave velocity (PWV). Both have been shown to have an independent predictive value in cardiovascular risk stratification. However it is not yet clear whether they are actually present and detectable in SSc patients, or if an association with a specific subtype exists (1). Objectives: to evaluate the presence of subclinical cardiac organ damage in patients with limited and diffuse SSc, in comparison with a cohort of healthy individuals. Methods: Patients with limited and diffuse SSc referred to the Rheumatology Unit in our Hospital, in according to 2013 ACR/EULAR Classification Criteria, were enrolled. The study was conducted in accordance with the Declaration of Helsinki and approved by our Ethics Committee. All patients underwent a complete transthoracic echocardiogram, and PWV evaluation, which were performed in agreement with the last International Guidelines (2). Past medical history and risk factors, clinical and biochemical data were collected. 23 healthy subjects, similar for demographic characteristics, were used as controls. Results: 41 patients (35 female, age 56.9±13.6 years), 21 with diffuse and 20 with limited SSc were recruited. Past medical history, cardiovascular risk factors, gender distribution and disease duration were similar in the two subgroups with no statistically differences. Patients with limited SSc were mean of 10 years older than patients with diffuse SSc. TEE parameters – left ventricular remodeling, atrial enlargement, diastolic disfunction - and hemodynamic indexes – PWV (6.5 [6;6.8] vs 7.0 [6.2;8.5], p=0.24) and Augmentation index (145.6±14.2 vs 149±20.6, p=0.52) did not show significant difference. Indeed, in the regression analysis, PWV was correlated to age (rho=0.60, p<0.001). When compared with healthy controls, again no significant difference emerged, considering echocardiographic and hemodynamic indexes. Conclusions: In SSc, PWV seems to increase in according to age, with no additional impact of the specific pathology nor subtype. Vascular damage in the SSc population is likely not reflected in increased arterial stiffness or subclinical cardiac damage. Evaluation of SSc patients with PWV and TEE should not be routinely performed. References: Ngian GS, Sahhar J, Wicks IP, Van Doornum S. Arterial stiffness is increased in systemic sclerosis: A cross-sectional comparison with matched controls. Clin Exp Rheumatol 2014;32(6 Suppl 86):S-161–6. Lang RM, Badano LP, Mor-Avi V, Afilalo J, et al. Recommendations for cardiac chamber quantification by echocardiography in adults: An update from the american society of echocardiography and the european association of cardiovascular imaging. J Am Soc Echocardiogr 2015, Jan;28(1):1–39.e14. Disclosure of Interest: None declared